Mystery of the brain metastatic disease in breast cancer patients: improved patient stratification, disease prediction and targeted prevention on the horizon? - Polivka, Jiri; Kralickova, Milena; Polivka, Jiri; Kaiser, Christina; Kuhn, Walther; Golubnitschaja, Olga (The EPMA journal, 2017)
The breast cancer (BC) diagnosis currently experiences the epidemic evolution with more than half of million deaths each year. Despite screening programmes applied and treatments available, breast cancer patients frequently develop distant metastases. The brain is one of the predominant sites of the metastatic spread recorded for more than 20% of BC patients, in contrast to the general population, where brain tumours are rarely diagnosed. Although highly clinically relevant, the brain tumour mystery in the cohort of breast cancer patients has not been yet adequately explained. This review summarises currently available information on the risk factors predicting brain metastases in BC patients to motivate the relevant scientific areas to explore the data/facts available and elucidate disease-specific mechanisms that are of a great clinical utility.
Keywords: Multilevel diagnostics; Breast cancer; Risk factors; Predictive preventive and personalised medicine; Patient stratification; Brain metastasis